The Emotional Development of Late Adolescents and Its Impact on Religious Education - Azep Maulana; Siti Roudhotul Jannah; Miswanto Miswanto; Bejo Bejo (International Journal on Advanced Science, Education, and Religion, 2024)
The aim of this research is to look at the emotional development of teenagers and the impact of Islamic religious education because many teenagers today cannot control their emotions when they speak and behave. This research uses a qualitative approach, which is a type of literature study. Sources of information about data collection techniques can be found in relevant literature, such as journals, books, documents and online literature. The results of this research show that emotional development during late adolescence is a process of emotional maturity, which causes teenagers to behave more realistically and not be reckless when making decisions. The emotional patterns of late adolescents are not much different from the emotional patterns of children; however, what differentiates them is the stimulus that causes their emotions to increase. Islamic education has a significant impact on the emotional development of young adolescents. Keywords: Emotional Development, Development of Late Adolescents, Emotional Development